2015
DOI: 10.15361/1984-5529.2015v43n3p280-286
|View full text |Cite
|
Sign up to set email alerts
|

Soil fauna under eucalypt stands of different ages in the Savanna of Piauí

Abstract: The reforestation with eucalyptus has increased significantly in the Brazilian Savanah and it can promote changes on soil biological properties, mainly soil fauna. Thus, the aim of this study was to evaluate the composition of soil fauna in areas with Eucalyptus plantations of different ages compared with native savanna. The study was conducted in Eucalytptus plantations aged one, two, three and four years and area with native forest was taken as reference. Soil fauna was collected in the dry and rainy season … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In relation to the diversity index of Shannon, eucalyptus and forest showed higher values in the two seasons probably due to the greater contributions of organic residues in the soil that favors the conditions of shelter, feeding and reproduction and creates larger ecological niches, as also verified by Cortes et al (2015). On the other hand, the soybean management system showed higher values of the Pielou index, which represents the uniformity of the distribution of the number of individuals in the different groups in each area.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In relation to the diversity index of Shannon, eucalyptus and forest showed higher values in the two seasons probably due to the greater contributions of organic residues in the soil that favors the conditions of shelter, feeding and reproduction and creates larger ecological niches, as also verified by Cortes et al (2015). On the other hand, the soybean management system showed higher values of the Pielou index, which represents the uniformity of the distribution of the number of individuals in the different groups in each area.…”
Section: Resultsmentioning
confidence: 69%
“…In its turn, the Eucalyptus grandis Hill (ex Maiden), in which soil preparation in the region is limited to plowing and harvesting at the time of planting, provides a large amount of litter with low nutritional quality and high C / N ratio, which contributes to slow decomposition of the organic matter (Pulrolnik et al, 2009). For Cortes et al (2015) the large amount of litter generated by eucalyptus, provides certain environmental conditions favorable to the action of macro and microorganisms allowing rapid mineralization and maintaining soil nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of the Formicidae and Coleoptera groups in all systems is in line with the results found by Lima et al (2019), studying epigeal fauna in different management systems in the Piauí semi-arid region. Cortez et al (2015), also found a greater predominance of the groups of Formicidae and Coleoptera, when evaluating the epigeal fauna eucalyptus crop with different ages in the cerrado of Piauí. These authors attributed the results to greater resistance and adaptation of these groups to the climatic conditions the of region.…”
Section: Diversity E Population Of Faunamentioning
confidence: 76%
“…The importance of these invertebrates has been emphasized for maintaining soil quality and the environment in the Cerrado biome (Lima et al, 2019;Santos et al, 2016;Portilho et al, 2011;Silva et al, 2011). However, there is still a lack of information on their behavior in anthropized areas and especially with eucalyptus cultivation (Souza et al, 2016;Cortez et al, 2015;Vargas et al, 2013). Moreover, more studies are needed regarding areas involving production systems with the use of eucalyptus, both in monoculture and in integrated systems, aiming at understanding the effects of different management systems and land uses on epigeal fauna.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, Nunes et al (2012) found that management systems adopted with different forages favored the presence of many individuals and species richness of edaphic fauna. In relation to the planted forest of eucalyptus, Cortez et al (2015) observed that the large amount of burlap generated by the crop provides favorable environmental conditions for a greater diversity of soil fauna organisms.…”
Section: Introductionmentioning
confidence: 99%